2021
DOI: 10.1108/jwl-01-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric overview of the Journal of Workplace Learning

Abstract: Purpose This study aims to analyze the Journal of Workplace Learning (JWL), focusing on articles between 1997 and 2020. Specifically, this study will examine articles in JWL, themes in JWL and the influence of JWL. Design/methodology/approach This study adopts bibliometric analysis methods, with indicators such as total articles, total citations, citation per article, h-index, Citescore, citation per year and considers different dimensions, including the leading articles, the most productive and influential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This compares to 48% of entry-level roles and 41% of first-level manager positions in other industries. 10 Career advancement is an important factor that women engineers consider when choosing to stay in the engineering profession. A survey by the Society of Women Engineers (SWE) found that 24% of women attributed growth potential as the primary reason for staying with their current employer and another 23% indicated it was the empowering work culture at their organizations.…”
Section: Workplace Climate Affects Retention Of Women In Stemmentioning
confidence: 99%
“…This compares to 48% of entry-level roles and 41% of first-level manager positions in other industries. 10 Career advancement is an important factor that women engineers consider when choosing to stay in the engineering profession. A survey by the Society of Women Engineers (SWE) found that 24% of women attributed growth potential as the primary reason for staying with their current employer and another 23% indicated it was the empowering work culture at their organizations.…”
Section: Workplace Climate Affects Retention Of Women In Stemmentioning
confidence: 99%